Genome-Wide Identification and Functional Analysis of NADPH Oxidase Family Genes in Wheat During Development and Environmental Stress Responses - Hu, Chun-Hong; Wei, Xiao-Yong; Yuan, Bo; Yao, Lin-Bo; Ma, Tian-Tian; Zhang, Peng-Peng; Wang, Xiang; Wang, Peng-Qi; Liu, Wen-Ting; Li, Wen-Qiang; Meng, Lai-Sheng; Chen, Kun-Ming (Frontiers in Plant Science, 2018)
As the key producers of reactive oxygen species (ROS), NADPH oxidases (NOXs), also named respiratory burst oxidase homologs (RBOHs), play crucial roles in various biological processes in plants with considerable evolutionary selection and functional diversity in the whole terrestrial plant kingdom. However, little is known the phylogenesis and functions of this gene family in wheat. Here, total 46 NOX family genes were identified in wheat genome and these NOXs could be classified into three subgroups: typical TaNOXs, TaNOX-likes and ferric reduction oxidases (TaFROs). Phylogenetic analysis indicated that the typical TaNOXs might originate from TaFROs during evolution and the TaFROs located on Chr 2 might be the most ancient forms of TaNOXs. TaNOXs are highly expressed in wheat with distinct tissue or organ-specificity and stress-inducible diversity. A large-scale expression and/or coexpression analysis demonstrated that TaNOXs can be divided into four functional groups with different expression patterns under a broad of environmental stresses and different TaNOXs are coexpressed with different sets of other genes which are widely participated in lots of important intracellular processes such as cell wall biosynthesis, defense response and signal transduction, suggesting their vital but diversity roles in both the plant growth regulation and stress responses of wheat.